Severe Hiatal Hernia as a Cause of Failure to Thrive Discovered by Transthoracic Echocardiogram - Clint J. Moore; Devan A. Conley; Cristóbal S. Berry-Cabán; Ryan P. Flanagan (Case Reports in Pediatrics)
A newborn infant with failure to thrive presented for murmur evaluation on day of life three due to a harsh 3/6 murmur. During the evaluation, a retrocardiac fluid filled mass was seen by transthoracic echocardiogram. The infant was also found to have a ventricular septal defect and partial anomalous pulmonary venous return. Eventually, a large hiatal hernia was diagnosed on subsequent imaging. The infant ultimately underwent surgical repair of the hiatal hernia at a tertiary care facility. Hiatal hernias have been noted as incidental extracardiac findings in adults, but no previous literature has documented hiatal hernias as incidental findings in the pediatric population.